The synthesis of monomethoxy‐6‐methyl‐7H‐indeno[2,1‐c]quinolines - Quraishi M.A. (My University, 2025)
A series of monomethoxy‐6‐methyl‐7H‐indeno[2,1‐c]quinolines has been prepared by cyclization of the appropriate 1,3‐dioxoindan‐2‐yl‐ethylideneanilines, followed by Wolff‐Kishner reduction. Copyright © 1989 Journal of Heterocyclic Chemistry